Evaluation of the in vitro regeneration capacity in Brazilian industrial tomato - Fári, Miklós; Resende, Geraldo Milanez de; Melo, Natoniel Franklin de (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate the regeneration capacity of the IPA-5 andIPA-6 Brazilian industrial tomato (Lycopersicon esculentum Mill) cultivars using four compositions ofculture media described in the literature and five inoculation methods. A new variation of inoculation,the split cotyledon method, was also tested. The largest frequency of shoot bud formation was 100%in the case of IPA-5 and 65% in the case of IPA-6. To induce shoot elongation, it was necessary toaccomplish three subcultures of the explants presenting shoot buds. In the case of IPA-5, the numberof the obtained shoots was higher when the induction of shoot buds was accomplished in culturemedium containing BAP (2.5 mg L-1) and IAA (0.2 mg L-1) followed by three subcultures on zeatin(0.5 mg -1) containing medium. Using such protocol, the IPA-5 cultivar produced, on the average, 5.45elongated shoots through the split cotyledon method. That capacity exceeded significantly the trimmedcotyledon method, which produced 4.4 elongated shoots per explant. In the case of IPA-6, the bestcombination of culture medium and inoculation method produced 0.87 elongated shoot per explant.The elongated shoots were rooted and transferred to greenhouse.